Choice of law - Symeonides, Symeon, 1949- (New York, NY : Oxford University Press, 2016)
'Choice of Law' provides an in-depth sophisticated coverage of the choice-of-law part conflicts law (or private international law) in torts, products liability, contracts, forum-selection and arbitration clauses, insurance, statutes of limitation, domestic relations, property, marital property, and successions. It also covers the constitutional framework and conflicts between federal law and foreign law and explains the doctrinal and methodological foundations of choice of law and then focuses on its actual practice, examining not only what courts say but also what they do.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 6, 2016).
Keywords: Conflict of laws -- United States; Conflict of laws